Searching for the 'Grail' : Can Uganda's Land Support its Prosperity Drive? - World Bank (World Bank, Washington, DC, 2015)
Over the past twenty years, Uganda’s population density has been increasing rapidly, placing significant pressure on the use of land. Uganda now has a population density of 194 persons per square kilometer of arable land, compared to 80 in Kenya and 116 in Ghana. At present, the majority of Uganda’s population still lives in rural areas, where the main source of livelihood is agriculture. However, the proportion of the population living in urban areas has increased significantly and will continue to increase into the future, with urban centers being the main driver of economic growth and transformation into higher value added activities. The highest rates of growth in population density are recorded in Uganda’s central region. It is essential that Uganda changes the manner in which it manages its land if the majority of its population is to achieve a higher level of prosperity through the healthy transformation of the agricultural sector and a shift towards higher value, more productive economic activities more generally. Through the formulation and implementation of smart policies, Uganda can ensure that its land serves as a more productive asset that facilitates positive transformation and a diversification of the economic base. The achievement of these goals will require a comprehensive set of actions that will promote security of land tenure and reduce the rate of occurrence of conflicts and disputes caused by overlapping rights; promote the healthy development of rental markets for land; and strengthen the capacities of institutions responsible for the management of land administration. Failure to unlock the potential of land may result in a deceleration of growth and lack of progress towards prosperity. In addition, rather than driving equitable economic growth, the process of urbanization will result in dysfunctionality in the form of the proliferation of slums; increased congestion; and a deterioration in the quality of, or a failure to develop, infrastructure due to an escalation in the costs of construction and payment of compensation. Implementation of relevant up to date laws and policies has to be accelerated to make land in Uganda genuinely secure, transferable, marketable and supportive of economic development.